1951
DOI: 10.1002/pol.1951.120070609
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of acetaldehyde and crotonaldehyde catalyzed by aliphatic tertiary amines

Abstract: Acetaldehyde was condensed with acetaldol using triethylamine as the catalyst. The reaction products of the branch‐chained type were found to predominate. Acetaldehyde was polymerized by trimethylamine, triethylamine, tri‐n‐propylamine, and tri‐n‐amylamine to resinous materials possessing desirable film‐forming properties. Crotonaldehyde was polymerized by triethylamine to a resin similar in all respects to the product of acetaldehyde produced under similar conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1962
1962
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…S3), suggesting that ethanol formation is likely an electrochemical process under the conditions we used for COR experiments. Instead, these 1 H NMR experiments support a previous conclusion that acetaldehyde can be polymerized by homogeneous reactions in alkaline conditions (55,58), influencing product quantification for COR. Notably, these reactions appear to be reversible as acetaldehyde can be recovered by simply neutralizing the electrolyte with 0.1 M HCl (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 78%
“…S3), suggesting that ethanol formation is likely an electrochemical process under the conditions we used for COR experiments. Instead, these 1 H NMR experiments support a previous conclusion that acetaldehyde can be polymerized by homogeneous reactions in alkaline conditions (55,58), influencing product quantification for COR. Notably, these reactions appear to be reversible as acetaldehyde can be recovered by simply neutralizing the electrolyte with 0.1 M HCl (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 78%
“…These data are not consistent with the linear poly(viny1 alcohol)-type structure previously suggested (1) for I, but show that this product is a highly branched one and that the sodium amalgam catalyst does behave like the other bases known to promote the adolization of acetaldehyde. The extensive branching can arise from the higher reactivity in basecatalyzed reactions of the methylene protons with respect to the methyl group in the acetaldol molecule, in accordance with the results of other authors (6).…”
Section: Acetaldehyde Oligomers By Poly Condensationsupporting
confidence: 91%
“…Thus, both the selectivity and conversion yield are severely limited by the experimental conditions. Some progress was made in the pioneering studies by Ishii and co-workers with a homogeneous iridium catalyst, [Ir(cod) (acac)] (acac = acetylacetonate, cod = 1,5-cyclooctadiene), 42 where the basic iridium center acts as an active site stabilized by phosphine ligand. In this study, they reported n-butanol selectivity of up to 67% at 12% conversion.…”
mentioning
confidence: 99%